2016
DOI: 10.1007/s11255-016-1364-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high-flux hemodialysis with hemodialysis filtration in treatment of uraemic pruritus: a randomized controlled trial

Abstract: Our results demonstrate that HFHD has a better efficacy in the treatment of UP than HDF. HFHD has an exactly therapeutical efficacy in the UP associated with the inhibition of microinflammation state in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
(45 reference statements)
0
28
0
2
Order By: Relevance
“…Five studies (total n 5 312) compared the effects of hemodialysis prescription modification on uremic pruritus. 24,27,57,61,64 All measured pruritus using a visual analogue scale, 4 were parallel-arm studies, and 1 was a crossover study. Two studies examined the effects of high-flux hemodialysis.…”
Section: Trials Of Hemodialysis Prescription Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (total n 5 312) compared the effects of hemodialysis prescription modification on uremic pruritus. 24,27,57,61,64 All measured pruritus using a visual analogue scale, 4 were parallel-arm studies, and 1 was a crossover study. Two studies examined the effects of high-flux hemodialysis.…”
Section: Trials Of Hemodialysis Prescription Modificationmentioning
confidence: 99%
“…Two studies examined the effects of high-flux hemodialysis. 57,61 One compared the effects of using high-flux hemodialysis against hemodialysis filtration, 61 whereas the other compared it to a low-flux hemodialysis control. 57 Both determined that high-flux hemodialysis was significantly better in improving pruritus intensity.…”
Section: Trials Of Hemodialysis Prescription Modificationmentioning
confidence: 99%
“…109 In addition, an RCT has shown that high-flux haemodialysis is more effective in treating uraemic pruritus than haemodialysis filtration. 110 Secondary and tertiary hyperparathyroidism often accompany ESRD and may contribute to pruritus (see section 7.5).…”
Section: Uraemic Pruritusmentioning
confidence: 99%
“…Use of high-flux polyacrylonitrile membrane has been reported to alleviate the severity of pruritus [43]. Hemodialysis with the target of Kt/V ≥ 1.5 (K = dialyzer clearance of urea, t = dialysis time, V = volume of distribution of urea, approximately equal to patient’s total body water) [44], as well as the use of high-flux dialyzer, may play a role in reducing the severity of uremic pruritus [4446]. A search of published literature found that other factors that were found to be associated with CKD-aP were elevated blood urea nitrogen (BUN) [38, 47, 48]; crystal deposition of calcium and phosphate on skin (due to hypercalcemia and hyperphosphatemia) [49]; high aluminum level [50]; secondary hyperparathyroidism [47]; erythropoietin deficiency, high ferritin level, lower transferrin [30] and xerosis [51].…”
Section: Discussionmentioning
confidence: 99%